Evaluation of Morphological and Molecular Diversity among South Asian Germplasms of Cucumis sativus and Cucumis melo. (14th October 2012) - Zhang, Chi; Pratap, Arun S.; Natarajan, S.; Pugalendhi, L.; Kikuchi, Shinji; Sassa, Hidenori; Senthil, Natesan; Koba, Takato
Abstract : Cucumber, Cucumis sativus (2 n = 2 x = 14 ), and melon, Cucumis melo (2 n = 2 x = 24 ), are two common vegetable crops worldwide. The present study evaluated eighteen Cucumis accessions (nine C. sativus and nine C. melo ) that were collected from three South Asian countries that have the most diversity of Cucumis . Nine quantitative and twenty-three qualitative characteristics were measured. The values of fruit weight displayed the biggest divergence among the nine quantitative traits and much variation was displayed in twenty-three qualitative traits among eighteen accessions. For eight morphological quantitative traits other than fruit weight, eighteen accessions were divided into three groups by using Principle Component Analysis and K-means cluster analysis. Also, two chloroplast genes rbcL and matK of eighteen accessions were sequenced. Combined sequences were subjected to construct phylogenetic trees by Neighbor-Joining and Maximum Likelihood methods. Topologies of nine melon accessions were same in these two methods and nine cucumber accessions showed difference. The genetic distances among each of C. sativus and C. melo accessions were not high. We conclude that the genetic relationship among the eighteen accessions used in this study is not distant although they display significant morphological variations. The information on novel Cucumis germplasms provided here would contribute to breeding program as well as evolutional study in Cucumis .